RATIONALIZATION OF ROUTINE CROSSMATCHED BLOOD ARRANGEMENT FOR CAESAREAN DELIVERIES AND ANALYSIS OF RISK FACTORS REQUIRING BLOOD TRANSFUSION: Risk Factors Associated with Blood Transfusion - Bajwa, Saleem Parvez; Haider, Sayyad Muhammad Zaheer; Safdar, C. Aqeel; Masood, Saima; Shehzad, Farrukh; Hameed, Mubashar; Raza, Hassan (Pakistan Armed Forces Medical Journal, 2015)
Objective: To assess the incidence of blood transfusions required in Caesarean section (CS) and evaluate the rationale of routinely arranging cross matched blood for every patient. Study Design: A chart review retrospective descriptive study. Place and Duration of Study: This study was conducted at the Anesthesia Department of Combined Military Hospital (CMH), Lahore, from June 2011 to May 2013. Patients and Methods: In this retrospective study we reviewed all singleton CS performed using data from blood bank registry and all CS patient’s charts obtained from the Records Department of the hospital. Clinical variables including demographic characteristics, estimated blood loss, indications for CS, preoperative haemoglobin and indications for transfusion were gathered. Patients transfused with blood had their medical records reviewed by two reviewers to confirm accuracy and identify risk factors for haemorrhage. Results: A total of 6250 caesareans deliveries were performed over the study period. Out of these 381 patients were transfused (6.09%). Blood typing and screening was done for 3260 cases (52%) and blood was arranged for 2320 (37%). Among blood receiving patients 250 patients (65.62%) were emergencies. Ninety eight patients (25.72%) were primigravida. Indications for transfusion mentioned in the charts were preoperative anaemia (18.37%), repeat caesarean sections (39.37%), placenta previa (6.56%), severe preeclampsia (17.06%), failed progress in labor and other rare causes (18.37%). Conclusion: Transfusion risk in patients undergoing routine CS is low. Factors indicating risk for transfusion include preoperative anaemia, repeat caesareans, severe preeclampsia, obstructed labor and placenta previa. In the absence of these risk factors routine arrangement of the blood does not enhance patient care.